Stratégies et modèles nationaux de croissance. - Michel Freyssenet (Revue de la Régulation)
This article proposes a new approach to identify and to characterize the national models. This approach consists first in determining the stake which binds the collective actors between them, second in answering the logical questions set by this stake to face it. It seems that in all the cases the growth, after redefinition, is the condition of the independence and the unity of the nations. The adopted main growth source imposes a rule to balance production and distribution, implies external and internal conditions of possibility, and demands coherent means to be exploited. The political compromises, necessary to find solutions to these requirements, appear to draw the national models, which limit the possible profit strategies for the capitalist firms.